Investment and financing decisions with learning-curve technology - Sarkar, Sudipto; Zhang, Chuanqian (Journal of Banking & Finance, 2020)
The learning curve has a significant impact on production cost (hence corporate profit) in a number of industries. While the learning curve is well recognized in the Economics literature and its effect on operating costs and production decisions widely studied, its effect on corporate investment has been largely unexplored. To our knowledge, there is one paper that examines this issue, but it is limited to unlevered firms. We therefore examine a levered firm's optimal investment and financing choices when using learning-curve technology. The main findings are as follows. The effect of leverage on the investment decision depends on the level of debt. Using the optimal debt level will result in earlier and larger investment. Thus, leverage has a positive effect on investment overall, and the difference between levered and unlevered firm is an increasing function of learning speed. The optimal leverage ratio (without a borrowing constraint) is an increasing function of learning speed. With a borrowing constraint, the investment decision is similar to the unconstrained-borrowing case, but the leverage ratio is initially increasing and subsequently decreasing in learning speed. Moreover, it is a decreasing function over a wider range for a more stringent borrowing constraint, for decreasing-returns-to-scale technology and for a less volatile product market.